Research Trends in Scaffolding Inquiry Models Integrated with Local Wisdom on Student Scientific Creativity: Bibliometric Analysis 2020-2025 - Ferniawan, Ferniawan; Ramdani, Agus; Rokhmat, Joni; Jufri, A Wahab; Sukarso, AA (International Journal of Science Education and Science, 2025)
Higher education has an important role in developing students' scientific creativity to face the challenges of the 21st century. One approach that has received attention in improving scientific creativity is the scaffolding inquiry model integrated with local wisdom. However, research related to the trend and direction of the development of the scaffolding inquiry model integrated with local wisdom on student scientific creativity is still limited. This study aims to provide a bibliometric review of the research trends of the scaffolding inquiry model integrated with local wisdom on student scientific creativity during the period 2020-2025. Data was obtained through Google Scholar using analysis tools such as Publish or Perish and Dimensions.ai, resulting in 1,000 documents selected based on PRISMA guidelines. Analysis was conducted using bibliometric methods and content analysis, supported by VOSviewer software to visualize keyword trends and research patterns. Research trends showed variations in the number of annual publications, with a significant spike in 2021 and a decline in subsequent years. Bibliometric analysis shows the dominance of publications in the form of books and monographs, highlighting the need for further exploration in this topic. Although the publication trend shows a decline in recent years, the scaffolding inquiry model integrated with local wisdom remains important to enhance students' scientific creativity. The integration of local wisdom in learning can create a more contextualized and innovative learning experience, support the development of scientific creativity skills, and fit the needs of 21st century education. Further research in the future is expected to explore more deeply the potential of technology and local wisdom in enric hing this learning model.